TVRI Sulbar Program In Preserving Mandar Culture In West Sulawesi - Rahmayani, Rahmayani; Ramli, Ramli; Qadaruddin, Muhammad; Iskandar, Iskandar; Halim, Abd (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This research uses agenda setting theory as a way to look at the production process of local TVRI West Sulawesi broadcasts, starting from the design process to the broadcast stage and then looking at the public response to cultural broadcasts broadcast by TVRI West Sulawesi, as well as using hypodermic (syringe) theory to look at the factors. supporters and obstacles to TVRI West Sulawesi in broadcasting Mandar cultural content in West Sulawesi. The data sources for this research are employees of TVRI West Sulawesi, KPID West Sulawesi, humanists and broadcasting academics. Data collection methods used in research are observation, interviews and documentation. The data collection technique used is the inductive method. The results of this research show. TVRI West Sulawesi does not yet have a special cultural program, TVRI. The TVRI West Sulawesi program with a cultural theme comes from the national program, namely Indonesian Charm, the theme is dominated by cultural themes, the Indonesian Charm program is broadcast once a month and the program model is a documentary. The supporting factors for TVRI West Sulawesi in its cultural content are program support from TVRI Nasional and the inhibiting factors are human resources, budget and competition.